Women's Economic Empowerment in Latin America and the Caribbean : Policy Lessons from the World Bank Gender Action Plan - World Bank (Washington, DC, 2014)
Group s gender action plan (GAP) trust fund has financed a series of programs to promote gender equality by empowering women to compete in key markets: land, labor, agriculture, finance and the private sector. Work and family: Latin American and the Caribbean women in search of a new balance offer new analysis of how household decision-making and allocation of resources affects female labor market outcomes in the region. This project summarizes over half a decade of gender-related activities, training, research and results in Latin America and the Caribbean. All of the GAP-funded cases chosen for this project provide succinct policy lessons that were: innovative; results-driven (impact was measured or documented); policy relevant (clear indications for policy makers); methodologically strong; have potential for scaling up or replication. The chapters present policy lessons organized around four themes of vital importance to women and their families: (A) access to labor markets; (B) improved workplace conditions, (C) entrepreneurial and income-earning opportunities, and (D) increased land titling and agricultural productivity. And this project includes five chapters: chapter one is key issues for women s economic empowerment in Latin; chapter two is boosting women s labor force participation; chapter three is good gender practices in the workplace; chapter four is promoting income-generating opportunities in urban and rural contexts; chapter five is women s productivity in agriculture.